Setting the foundation for renewal: restoring sponge communities aids the ecological recovery of Florida Bay. Issue 12 (12th December 2021) - Butler, Jack; Sharp, William C.; Hunt, John H.; Butler, Mark J.
Abstract: Coastal ecosystems are constantly buffeted by anthropogenic forces that degrade habitats and alter ecological processes and functions; in turn, this habitat degradation diminishes the ecosystem goods and services on which humans rely. Within the last few decades, the field of restoration ecology has burgeoned into a discipline that marries scientific rigor with functional restoration practice—an idea championed by Pete Peterson and his research. Here, we describe our efforts to restore the hard‐bottom sponge communities of Florida Bay, FL (USA)—a once‐diverse subtropical lagoon severely degraded by cyanobacteria blooms—and the scientific and practical lessons learned from those efforts. Sponge community restoration yielded insights into basic sponge biology and ecology (e.g., density‐dependent growth rates) and hastened the recovery of ecological processes (e.g., rates of sedimentation, structuring of water column characteristics, soundscape productions). Because the results of our initial restoration efforts were promising, our collaboration among academic researchers, natural resource managers, and non‐governmental organizations has begun scaling up restoration efforts to re‐establish the sponge communities over large areas of degraded hard‐bottom to "jump start" the ecological recovery of Florida Bay. Though our efforts show promise for ecological recovery, restoration will require a concerted effort by scientists, resource managers, and citizens to stem the anthropogenic drivers of ecological degradation of this unique South Florida ecosystem.